Teachers' and mental hygienists' reactions to behavior problems of elementary school children - Agno, Lydia (Navarro) 1932- (s.n.], 1964)
This study designed a measurement of teachers' and mental hygienists' reactions to the nature of the pupils' behavior problems which were officially referred to guidance counselors. The behavior problems of the children, teachers' reactions to the degree of seriousness of the behavior problems, the mental hygienists' reaction to the degree of seriousness of the behavior problems, and the differences of the reaction of teachers and mental hygienists with regards to the seriousness of the problem were specifically determined in this study.